PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIC AUDITORY VISUAL INTELLECTUALY) TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Nana Sutarna (Universitas Muhammadiyah Surakarta, 2018)
The research aims to find out how the influence of SAVI model (somatic auditory visual intellectualy)) in terms of student learning outcomes in the fourth grade of social studies subjects social problems in the State Elementary School Cimulya District Cimahi Kuningan. This study is an experimental research with quantitative approach, While the sample used in this study amounted to 32 students, Methods of data collection of IPS learning results using multiple choice test and student skill observation. The data analysis technique used in this research is normality test, homogeneity test of two variance, and hypothesis test (t test) used to know the influence of SAVI learning model (somatic auditory visual intellectualy) in terms of student learning result of grade IV in subject matter social studies Social in State Elementary School Cimulya District Cimahi Kuningan. Based on statistical perceptions obtained obtained value t_hitung = 31.66, while from table t distribution at significance level α = 0.05, obtained value t_ (0.95 (62)) = 1.999. Since 31.66 1.999 or t_count〖t〗 _ (1- α) then H_0 is rejected or H_1 is accepted. This means that there is an increase in student learning outcomes after applying SAVI learning model (somatic auditory visual intellectualy) on social science subjects (IPS) social problem material in class IV Cimulya State Elementary District Cimahi District Kuningan